2017
DOI: 10.1016/j.scitotenv.2017.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants in the Olifants River Basin, South Africa: Bioaccumulation and trophic transfer through a subtropical aquatic food web

Abstract: This study investigates the trophic transfer of persistent organic pollutants (POPs: PCBs, PBDEs, OCPs and PFASs) in the subtropical aquatic ecosystem of the Olifants River Basin (South Africa) by means of trophic magnification factors (TMFs). Relative trophic levels were determined by stable isotope analysis. POP levels in surface water, sediment and biota were low. Only ∑DDTs levels in fish muscle ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 61 publications
7
24
0
1
Order By: Relevance
“…To our knowledge, only four studies have been performed on aquatic biota in Africa, with only one in fish. Verhaert et al (2017) detected relatively low PFAS concentrations in liver and muscle tissue of fish from the Olifants River basin in South Africa. In addition, a study on PFASs in South African crocodiles in Kruger National Park detected multiple PFASs in relatively high concentrations and suggested a point source for PFOS contamination of this area (Christie et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, only four studies have been performed on aquatic biota in Africa, with only one in fish. Verhaert et al (2017) detected relatively low PFAS concentrations in liver and muscle tissue of fish from the Olifants River basin in South Africa. In addition, a study on PFASs in South African crocodiles in Kruger National Park detected multiple PFASs in relatively high concentrations and suggested a point source for PFOS contamination of this area (Christie et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Data on PFAS concentrations in water of aquatic systems in Africa are very scarce. Only two studies could be found in South African river water (Mudumbi et al, 2014a;Verhaert et al, 2017), in which PFOA and PFOS were detected in concentrations up to 314 and 182 ng/L in the Diep River, 390 and 47 ng/L in the Salt River and 146 and 23 ng/L in the Eerste River, respectively (Mudumbi et al, 2014a). In the Olifants River basin all surface water concentrations of PFAS were <LOQ (Verhaert et al, 2017).…”
Section: Abiotic Environmentmentioning
confidence: 99%
“…The study is also aimed to ascertain whether the concentrations of Total Hg are compliant with the maximum values in fishery products established by the European Legislation. Taking into account the role of biotic and abiotic factors in the accumulation of these pollutants in fish (Verhaert et al, 2017 andStorelli et al, 2002), the dependences between pollutant concentrations, fish species and specimen weight have been also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the presence of agrochemicals in many South African rivers has been well-documented (e.g. the uMngeni River ( Gakuba et al , 2018 ), Olifants River ( Verhaert et al , 2017 ), Buffalo River ( Yahaya et al , 2017 ), Luvuvhu and Letaba rivers ( Gerber et al , 2015 ), Vaal River ( Quinn et al , 2009 ), Lourens River ( Bollmohr et al , 2007 ) and the Msunduzi River ( Adeyinka et al , 2019 )). Yet, there is little research regarding the ecological impact of many of the registered products in the environment ( Van der Laan et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%